Labor and punishment work in and out of prison - Hatton, Erin Elizabeth, 1974- (University of California Press, 2021)
"The insightful chapters in this volume reveal the multiple and multifaceted intersections between mass incarceration and neoliberal precarity. Both mass incarceration and the criminal justice system are profoundly implicated in the production and reproduction of the low-wage "exploitable" precariat, both within and beyond prison walls. The carceral state is a regime of labor discipline-and a growing one-that extends far beyond its own inmate labor. This regime not only molds inmates into compliant workers willing and expected to accept any "bad" job upon release but also compels many Americans to work in such jobs under threat of incarceration, all the while bolstering their "exploitability" and socioeconomic marginality"--